Research on gas-liquid coupled flow field dynamics and atomization characteristics of multi-duct sprayers based on CFD - Li, Jun; He, Hongwei; Fan, Hongtao; Lie, Yilin; Li, Yuhao; Cao, Yachao (Frontiers in Plant Science, 2025)
This study addresses the issues of prolonged testing cycles and high costs associated with traditional sprayers. Using Computational Fluid Dynamics method, a simulation model of the gas-liquid coupling flow field for multi-duct sprayer was established, and the effects of operational parameters, the air outlet opening angle, interval, and air velocity on droplet deposition and atomization characteristics were systematically investigated. A multi-factor simulation test was conducted by constructing a CFD simulation model, performing multi-polyhedron meshing, and applying the RNG k-ϵ turbulence model along with the Discrete Phase Model. The results demonstrate that as the flow rate increases from 0.03 kg/s to 0.06 kg/s, the mean thickness of the liquid film and the uniformity index of its distribution both increased, from 197.3 μm and 0.7521 to 340.71 μm and 0.8465 respectively. Medium spray angles and small inner diameter nozzles optimize the uniformity of liquid film distribution, indirectly revealing the effects of each parameter on droplet deposition and its distribution uniformity. When the air outlet opening angle increases from 70° to 80° and then to 90°, the effective working height of the airflow field increases by 0.2 m and 0.1 m, respectively. However, increasing the interval leads to a decrease in the uniformity of the end velocity. The droplets undergo two atomization events within the airflow field. Following the first atomization, the particle size increases due to collisions and merging. The secondary atomization, occurring at a distance of 1.2 m from the air outlet, reduces the particle size and enhances deposition efficiency. Furthermore, as the initial air velocity decreases, the particle size of the droplets within the airflow field tends to increase. The reliability of the CFD simulation model developed in this study were validated through a droplet particle size measurement test. The test results demonstrated that the trend of the measurement values aligned with the simulation values, with the relative error ranging from 11.4% to 15.3%. This research reveals the gas-liquid coupling mechanism within the multi-duct spray flow field, providing a theoretical foundation for the further optimization and modification of this sprayer, thereby significantly reducing costs and improving efficiency.